ITS2-rDNA Sequence Variation of Phlebotomus sergenti s.l. (Dip: Psychodidae) Populations in Iran - Vahideh Moin-Vaziri; Mohammad Ali Oshaghi; Mohammad Reza Yaghoobi-Ershadi; Pupak Derakhshandeh-Peykar; Mohammad Reza Abaei; Fatemeh Mohtarami; Ali Reza Zahraei-Ramezani; Aboulhassan Nadim (Tehran University of Medical Sciences, 2016)
Background: Phlebotomus sergenti s.l. is considered the most likely vector of Leishmania tropica in Iran. Although two morphotypes- P. sergenti sergenti (A) and P. sergenti similis (B)-have been formally described, further morphological and a molecular analysis of mitochondrial cytochrome oxidase I (mtDNA-COI) gene revealed inconsistencies and suggests that the variation between the morphotypes is intra-specific and the morphotypes might be identical species. Methods: We examined the sequence of the ITS2-rDNA of Iranian specimens of P. sergenti s.l., comprising P. cf sergenti, P. cf similis, and intermediate morphotypes, together with available data in Genbank. Results: Sequence analysis showed 5.2% variation among P. sergenti s.l. morphotypes. Almost half of the variation was due to the number of an AT microsatellite repeats in the center of the spacer. Nine haplotypes were found in the species constructing three main lineages corresponding to the origin of the colonies located in southwest (SW), northeast (NE), and northwest-center-southeast (NCS). Lineages NCS and NE included both typical P. cf sergenti and P. cf similis and intermediate morphotypes. Conclusion: Phylogenetic sequence analysis revealed that, except for one Iranian sample, which was close to the European samples, other Iranian haplotypes were associated with the northeastern Mediterranean populations including Turkey, Cyprus, Syria, and Pakistan. Similar to the sequences of mtDNA COI gene, ITS2 sequences could not resolve P. sergenti from P. similis and did not support the possible existence of sibling species or subspecies within P. sergenti s.l..